Prophetic Medicine (Twibb Nabbawi) Principles in Clinical Practice: Experiences From Uganda - Rashid, Naziru (International Journal of Human and Health Sciences (IJHHS), 2024)
Prophetic medicine (Twibb Nabbawi) refers to the advice, the teachings and practices given by the prophet Muhammad (PBUH) regarding disease prevention and treatment as found in both the Quran and the hadith. These include preventive, promotive and therapeutics modalities. They range from hygiene and behavioral practices, dietary/nutritional practices as well as exercises among others. Several countries especially in the middle east, far east, some countries in Europe and America have embarked on the reactivation, research and practice of this noble principles in enriching the medical knowledge as well as the clinical practice of prophetic medicine. This current paper presents the experiences of use and practice of prophetic medicine principles and teachings in Uganda. They also range from preventive, promotive and therapeutic modalities and varies from various health facilities and individual Muslim health professionals under the umbrella of the Islamic Medical Association of Uganda. (IMAU). In conclusion, prophetic medicine is a critical component of clinical care practice that should be adopted for healthcare delivery. Healthcare professionals should adopt its practice to ensure holistic healthcare service delivery. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 241-248